Exploring Students' Ethical and Social Responsibilities in Academic Behavior and Community Impact - Sri Buwono; Venny Karolina; Hadi Wiyono; Fithra Ramadian; Carla Queiroz; Toby Xaixanith (Yayasan Keluarga Guru Mandiri, 2025)
This study explored students' ethical and social responsibilities in academic and community settings, emphasizing the interplay between ethical awareness and social engagement. Ethical responsibility included adherence to academic integrity policies, respect for intellectual property, and institutional conduct codes, while social responsibility involved participation in volunteer work, leadership, and advocacy for diversity. Using a mixed-methods approach, this research integrated quantitative analysis from structured questionnaires and qualitative insights from in-depth interviews with students from higher education institutions in Indonesia. The findings revealed a strong correlation between ethical and social responsibilities, where students with higher ethical awareness demonstrated greater social engagement. However, social responsibility remained moderate, suggesting further institutional support was needed. Gender differences indicated that male students showed slightly higher social responsibility levels than females. This study contributed to educational policies by offering a framework to strengthen ethical integrity and civic involvement, ensuring students were prepared for academic and professional ethical challenges. The results could guide curriculum development and institutional strategies to foster responsible academic practices, ultimately shaping students into morally and socially responsible individuals.